LATIHAN AEROBIK INTENSITAS SEDANG DENGAN DIET RENDAH KOLESTEROL LEBIH BAIK DALAM MEMPERBAIKI KOGNITIF DARIPADA INTENSITAS RINGAN PADA PENDERITA SINDROMA METABOLIK - Ratmawati, Yuliana; Pangkahila, Alex; Lesmana, S. Indra (Sport and Fitness Journal; Volume 1, No.2, 2013, 2013)
Metabolic syndrome is a group of risk factors causing atherosclerosis. The presence of cholesterol mikroemboli carotid plaque is considered as one of the mechanisms that can interfere with cognitive. Aerobic exercise is one of the interventions that can improve cognitive function. The purpose of this study was to determine the aerobic exercise of moderate intensity with more cholesterol diet improve cognitive rather than light intensity in patients with metabolic syndrome. The experimental research method to design randomized control trial of pre and post test design. Sample of 26 patients with metabolic syndrome. samples were divided into two groups. The first group was given exercise intensity light with a low cholesterol diet (n = 13) while the second group was given moderate intensity exercise with low-cholesterol diet (n = 13).Characteristics of study subjects with age range of 45-55 years old, with a body mass index 23-29 range. Data before and after the treatment with a light intensity aerobic low cholesterol diet obtained p> 0.05 normally, while the data before and after the treatment of moderate-intensity aerobic with low cholesterol diet p <0.05 distribution is not normal. Different test groups before and after treatment with a mild intensity aerobic low cholesterol diet using paired sample t-test test showed 0,001 (p <0,05). Different test before and after the treatment of moderate-intensity aerobic with low cholesterol diet results obtained using the Wilcoxon Sign Rank Test 0,001 (p <0,05). Different test groups after the treatment of mild and moderate intensity aerobics with low cholesterol diet results obtained using the Mann-Whitney U 0,005 (p <0.05) there is a significant difference between treatment groups with a light aerobic low-cholesterol diet with moderate intensity aerobic treatment group with a low-cholesterol diet. The conclusion of this research is that the treatment group showed moderate aerobic intensity with a low cholesterol diet improve cognitive more than mild intensity aerobics with low-cholesterol diet.
Keywords: metabolic syndrome, cognitive function, aerobic exercise